2004
DOI: 10.1002/bip.10560
|View full text |Cite
|
Sign up to set email alerts
|

Brownian dynamics of interactions between glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH) mutants and F‐actin

Abstract: Brownian dynamics simulations of computer models of GAPDH mutants interacting with F-actin emphasized the electrostatic nature of such interactions, and confirmed the importance of four previously identified lysine residues on the GAPDH structure in these interactions. Mutants were GAPDH models in which one or more of the previously identified lysines had been replaced with alanine. Simulations showed reduced binding of these mutants to F-actin compared to wild-type GAPDH. Binding was significantly reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…BD methodology and the program MacroDox have been used successfully to study the cyt f-PC and cyt f-cyt c 6 interactions (9)(10)(11)38,40) plus the interactions between other proteins (58,59). For a description of the MacroDox strengths and weaknesses, see Gross and Pearson (10), Haddadian and Gross (11), and Gross (40).…”
Section: Brownian Dynamics Simulationsmentioning
confidence: 99%
“…BD methodology and the program MacroDox have been used successfully to study the cyt f-PC and cyt f-cyt c 6 interactions (9)(10)(11)38,40) plus the interactions between other proteins (58,59). For a description of the MacroDox strengths and weaknesses, see Gross and Pearson (10), Haddadian and Gross (11), and Gross (40).…”
Section: Brownian Dynamics Simulationsmentioning
confidence: 99%
“…They are found externally projected and two of these side chains (that is, amino acid residues Lys-24 and Lys-69) form a patch. In a study using molecular dynamics simulations of computer models [20], the authors observed that single and double mutants (i.e. substitutions with alanyl residues) did not have a large effect on the average electrostatic binding energy, suggesting that the lysine residues act in concert.…”
mentioning
confidence: 98%
“…GAPDH was demonstrated as tubulin-binding protein ( Tisdale et al, 2009 ; Landino et al, 2014 ). Similarly, GAPDH is also bound to actin ( Waingeh et al, 2004 ). In mouse cell lines, GAPDH interacts with lactoferrin ( Chauhan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%